Analysis of The Influences of Regulatory Support and Customer Relationship Management on Green Transportation Throught Cost efficiency at PT Pos Indonesia - Rahman Fathan; Maniah Maniah; Erna Mulyati (Siber Journal of Transportation and Logistics, 2026)
This study aims to analyze the influence of regulatory support and customer relationship management on green transportation implementation through cost efficiency as a mediating variable at PT Pos Indonesia (Persero). The research is motivated by the increase in logistics activities due to the growth of e-commerce, which drives distribution needs while simultaneously intensifying the challenge of reducing carbon emissions in the transportation sector. The study employs a quantitative approach with descriptive and verificative methods. Data were obtained through questionnaires distributed to 200 employees of PT Pos Indonesia (Persero) in various regions of Indonesia using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that regulatory support has a positive and significant effect on cost efficiency (β = 0.544; t = 12.727) and green transportation implementation (β = 0.482; t = 9.527). Customer relationship management also has a positive and significant effect on cost efficiency (β = 0.449; t = 8.948) as well as on green transportation implementation (β = 0.333; t = 6.780). In addition, cost efficiency has a positive effect on green transportation implementation (β = 0.288; t = 5.935) and partially mediates the influence of both independent variables on green transportation implementation. This study is expected to serve as a reference for the development of green logistics and the implementation of green transportation at PT Pos Indonesia (Persero).